2014
DOI: 10.1111/appy.12125
|View full text |Cite
|
Sign up to set email alerts
|

Effect of maternal anxiety on maternal serum and fetal cord blood cortisol

Abstract: These data suggested that high maternal trait anxiety increases fetus cord blood cortisol and may regulate fetal growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 18 publications
(19 reference statements)
0
10
0
2
Order By: Relevance
“…Not less important for an optimal pregnancy is a healthy psychological status [ 31 , 32 , 96 ]. In that sense, exercise represent an excellent opportunity to improve quality of life [ 33 ] and reduce cortisol levels, which may in turn have a positively influence on the foetus and child [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Not less important for an optimal pregnancy is a healthy psychological status [ 31 , 32 , 96 ]. In that sense, exercise represent an excellent opportunity to improve quality of life [ 33 ] and reduce cortisol levels, which may in turn have a positively influence on the foetus and child [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…An optimal mental health during pregnancy is also a major concern. High levels of depression or anxiety during gestation and post-partum affect maternal quality of life, and in turn, could have a negative influence on the foetal and child health [ 31 , 32 ]. Exercise may improve the pregnant quality of life and reduce stress [ 33 36 ], which might protect the foetus [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Glover et al [13] have shown a stronger correlation between maternal and fetal cortisol among more anxious pregnant women. In addition, Keshavarzi et al [7] have reported that higher maternal anxiety is associated with an increase in fetal cord blood cortisol.…”
Section: Discussionmentioning
confidence: 99%
“…Maltau et al [6] have shown that maternal anxiety is associated with reduced concentrations of estriol in maternal plasma. In addition, it has been documented that high maternal anxiety increases cortisol in maternal serum and also in fetal cord blood [7]. Other studies have reported that higher cortisol levels affect the syntheses or the serum levels of estriol, AFP, and inhibin [8,9,10].…”
Section: Introductionmentioning
confidence: 99%